TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMALSUAN SURAT KETERANGAN SEHAT DI TENGAH WABAH COVID-19 BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA (Studi Kasus Putusan Nomor 102/Pid.B/2020/PN.Nga dan Putusan Nomor 138/Pid.B/2022/PN Klk) - Ahmad Badawi; Gledy Berliana (Nusantara Hasana Journal, 2022)
Crime is a social problem that occurs in the midst of society, because the perpetrators and victims are also members of the community. And it can be concluded that the crime will continue to run/develop along with the dynamics of people's lives. In Indonesian legal arrangements, the criminal act of forging letters is regulated in Articles 263 to 276 of the Criminal Code. The formulation of the research problem is (1) How is the application of the law to participate in the purchase of fake medical certificates, originally the witness became a suspect in the decision in Decision Number 102/Pid.B/2020/PN.Nga and Decision Number 138/Pid.B/2021/PN cl? (2) What is the difference between the elements of responsibility of the perpetrator in the act of falsifying medical certificates and the results of the antigen swab test in convicting criminal acts in the case of Decision Number 102/Pid.B/2020/PN.Nga and Decision Number 138/Pid.B/2021/ PN Klk The research method used is normative legal research. The nature of this normative research is descriptive. The approach used is a statutory approach and a case approach. The results of this study are (1) the judge ignores the participation of buyers or users of fake letters in Decision Number 102/Pid.B/2020/PN.Nga and Decision Number 138/Pid.B/2021/PN Klk. The judge should also look at the legal facts at trial. Based on the provisions of Articles 263 and 268 of the Criminal Code, in addition to the perpetrators of writing letters, users of health certificates are also threatened with the same sentence, namely 6 (six) years in prison. (2) The difference in the element of responsibility in this research case, namely Decision Number 102/Pid.B/2020/PN.Nga is subject to Article 268 of the Criminal Code and sentenced to the Defendants, namely 2 (two) years in prison. Meanwhile, Decision Number 138/Pid.B/2021/PN Klk is subject to Article 263 Paragraph (1) of the Criminal Code with imprisonment for 1 (one) year and 10 (ten) months. The author does not agree with the judge's verdict, it should be Decision Number 102/Pid.B/2020/PN. in the category of forgery of ordinary letters in general, namely Article 263 of the Criminal Code.